Diseño e implementación de una tostadora automática para el mejoramiento de la producción de cereales tostados en la microempresa Molinos San Luis. - Hurtado Ramírez, Edison Bladimir (2020)
The technological proposal has as to objective automate a cereal toaster machine, which allowed to obtain a uniform roast of cereals, the same that will be used for the production of flour and thus eliminate the fraction of grains that exceeded the term of roast subjected to a on exposure, in addition to highlighting the physical overexertion of the worker due to the lack of application of industrial processes. Analytical methods and observation techniques were applied to solve the problem and get the following results: minimum capacity 15Kg-lb and maximum capacity 23Kg-lb, temperature 150 - 175 ° C, roasting time 21 minutes and 29 minutes maximum capacity, blade speed 20 revolutions per minute. The cereal toaster machine removed the grains that exceeded the roasting limit by means of a mechanical operation based on a 1.5 HP gearmotor, with a pulley-type pulley and blade-driven system that moves the cereal, its operation automatic account of a temperature controller, a LOGO for the timing of the process, a rack-and-pinion lifting system and automatic opening of the roasting chamber by a DC motor, the construction material was made of AISI 304 stainless steel for its properties Exclusive for food production. After its implementation, a better production performance was evidenced by automating the process, thus greatly reducing the direct intervention by the operator during the cereal roasting process.